Wildlife Conservation and Management - Webster, Aubree (United States : Murphy & Moore Publishing, 2022)
The practice of conserving wild species with their habitats to prevent them from extinction is known as wildlife conservation. There are numerous threats that endanger the existence of wildlife. These include habitat destruction and fragmentation, illegal wildlife trading, overexploitation of wildlife, culling, pollution, etc. Wildlife management aims to balance the need of wildlife with that of humans. This field includes game keeping, pest control and wildlife conservation. Rewilding as a preservation technique is widely used for wildlife management along with reforestation. Diverse methods for wildlife conservation include wildlife population monitoring, establishment of protected areas, etc. This book is compiled in such a manner, that it will provide an in-depth knowledge about the theory and practice of wildlife conservation and management. It elucidates new techniques and their applications in a multidisciplinary approach. This book attempts to assist those with a goal of delving into the field of wildlife conservation and management.
Includes index.
Includes bibliographical references.
Keywords: Fragmented landscapes; Forest management; Wildlife conservation